A Chinese family with cat eye syndrome and abnormality of eye movement: First case report - Lu, Yang; Shen, Liping; Zheng, Yue; Zhang, Haichen; Liu, Yanbo; Qi, Ming; Huang, Shangzhi; Shen, Bo (Frontiers in Pediatrics, 2023)
Background: Cat eye syndrome (CES) is a rare disease with a wide spectrum of phenotypic variability, that observed in 1:150,000 newborns. CES is characterized clinically by the combination of iris coloboma, anal atresia, and preauricular tags and/or pits. There are many eye malformations been reported associated with CES, such as iris and chorioretinal coloboma. However, Abnormality of eye movement have not been previously reported. Case presentation: we reported a Chinese family carry a 22q11.1-q11.21 duplication of 1.35 Mb tetrasomy (chr22:17,249,959-18,599,906, hg19) in two generations. On the basis of proband and her father’s clinical manifestations, the diagnosis of CES with abnormality of eye movement was based on ophthalmological examination, cytogenetic analysis, FISH, CNV-seq and WES. Conclusion: Our findings broadened the symptom spectrum of CES syndrome and laid the foundation for the pathogenesis, diagnostic targets and drug research of abnormality of eye movement and was helpful for early diagnosis and intervention of CES.